Clinical and cognitive characteristics of Angelman syndrome - Đurić-Zdravković, Aleksandra; Japundža-Milisavljević, Mirjana; Maksimović, Ivana; Roknić, Ana (Specijalna edukacija i rehabilitacija, 2021)
Introduction. Angelman syndrome, as a rare genetic and neurodevelopmental disorder characterized by severe intellectual deficit and falling behind in psychomotor development, represents a challenge for adequate and correct creation of individual (re)habilitation procedure. More precise determination of cognitive and speech profile is difficult due to integrative hypermotor behavior and attention and speech deficits. Objective. The aim of this paper was to analyze and summarize empirical data on clinical, cognitive and speech characteristics of Angelman syndrome. Methods. A systematic review of the literature published in peer-reviewed publications, from 2001 to June 5, 2021, was performed by searching electronic databases available through the service of the Serbian Library Consortium for Coordinated Acquisition – KOBSON. A “hand search” (Research Gate and Google Scholar) was also used. Results. The analyzed results of the research indicate that the presence of sensorimotor schemes that represent cognitive structures of the earliest childhood is characteristic for Angelman syndrome. Receptive speech skills are more developed than expressive ones, which usually do not exist. Supportive therapy, which includes interventions in early childhood, speech therapy and occupational programs, is very important for treatment within this clinical picture. Conclusion. It is necessary to improve the process of assessing cognitive and speech skills due to the targeted creation of an individual cognitive-speech developmental profile. It is also crucial to identify urgent areas that require treatment and in which individual and family support should be provided.
Keywords: Angelman syndrome; intellectual disability; clinical characteristics; cognitive characteristics; speech; (re)habilitation